Developing a Trigonometry AR Book Using an Ethnomathematics Approach to Improve International Collage Students' Motivation and Learning Outcomes - Achmad Buchori; Farida Nursyahidah; Dina Prasetyowati; Sharifah Osman (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
This study presents the development of an Augmented Reality (AR)-based trigonometry learning media integrating ethnomathematics to enhance students’ conceptual understanding and engagement. The AR system was designed using the ADDIE framework, emphasizing the design and development stages, with validation conducted through expert review and limited user trials at Universitas PGRI Semarang (UPGRIS) and Universiti Teknologi Malaysia (UTM). The AR Book integrates local cultural geometries such as traditional architectural patterns and ornaments into interactive 3D visualizations to contextualize trigonometric concepts. The system was developed using Unity 3D and Vuforia SDK, optimized for Android devices. Validation results indicated high content validity (92%) and strong media practicality (88%), while small-scale implementation showed improved student motivation and learning outcomes. Beyond educational outcomes, the research contributes to the advancement of culturally adaptive AR learning media design and demonstrates the potential scalability of ethnomathematics-based AR systems in STEM education.